Rituals of the Past Prehispanic and Colonial Case Studies in Andean Archaeology - Bautista, Stefanie (University Press of Colorado, 2017)
Through the study of archaeological, ethnographic, linguistic, and historical evidence from northern Peru to northern Chile, Bolivia, and northwest Argentina, the authors in this volume show the significance of ritual from pre-contact to present day in the Andes. These volume essays deal with theoretical and methodological concerns in anthropology and archaeology including non-human and human agency, the development and maintenance of political and religious authority, ideology, cosmologies, and social memory, and their relationships with ritual action. By providing a diachronic and widely regional perspective on ritual in the Andes, this volume shows how ritual is both persistent and dynamic and is key in understanding many aspects of the formation, reproduction, and change of life in past Andean societies.